Improving the Cardiovascular Endurance of Teacher Education Students through the Utilization of the TikTok Application - Masangcay, Ivan B.; Parungo, John Paul A.; Cruz Jr., Salvador L. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Driven by the widespread usage of mobile applications, the expansive development of TikTok application has carried considerable challenges and opportunities to the Physical Education industry. Hence, it is imperative to examine the usefulness of this application to mitigate the low cardiovascular endurance of college students since the conduct of research to improve their physical activity engagement is still significant. Thus, this action research sought to improve the cardiovascular endurance of undergraduate teacher education students using the TikTok application as a tool for their physical activity. This study utilized a quantitative approach, specifically, the pretest-post-test design which is classified as quasi-experimental research. Using the normative data from YMCA 3-minute step test, 50 participants from the Bachelor of Elementary Education (BEEd) enrolled in their physical education classes were determined to be qualified based on their pre-test scorecards. Two groups were formed out of them: 25 in the experimental group who were exposed to the intervention and another 25 in the control group who were instructed using the standard discussion. Descriptive statistics and ANOVA-type test analysis were utilized using participants' pre-test and post-test results to ascertain the efficacy of the intervention. Results unveiled that the intervention has significantly improved the experimental group's post-test scores compared to the control group since the post-test results of the control group remained almost stagnant, indicating the intervention's effectiveness by rejecting the null hypothesis. Therefore, this action research inferred that the intervention has efficiently strengthened the cardiovascular endurance of the 1st year BEEd students.